Effects of ethyl carbamate and its metabolites on the antibody response in splenocyte cultures from female Balb/C mice - Jeong, TC; Kim, HJ; Cha, SW; Park, JI; Shin, HC; Kim, DH; Han, SS; Roh, JK (MARCEL DEKKER INC, 1996)
To investigate a possible role by cytochrome P450 (P450) in ethyl carbamate-induced immunosuppression, an attempt to assess the ability of ethyl carbamate, its metabolites produced by P450 (i.e., ethyl N-hydroxycarbamate and vinyl carbamate), and methyl carbamate to suppress the polyclonal antibody response induced by bacterial lipopolysaccharide was made in splenocyte cultures isolated from female Balb/C mice. The results showed that vinyl carbamate and ethyl N-hydroxycarbamate were more immunosuppressive compared to ethyl carbamate. A structurally related analogue, methyl carbamate, did not suppress the antibody response. These results indicate that metabolism of ethyl carbamate by P450 may produce more immunosuppressive metabolites as in ethyl carbamate-induced carcinogenicity. A pre-incubation study with phenobarbital-induced liver microsomes in the presence of NADPH-generating system showed that the antibody response was suppressed by ethyl carbamate when splenocytes were pre-incubated with ethyl carbamate and microsomes simultaneously. Moreover, the suppression was completely recovered by the addition of a P450 inhibitor, aminoacetonitrile, in the pre-incubation. Taken together, the present results indicate that metabolism of ethyl carbamate by P450 enzyme(s) may be an important pathway to cause immunosuppression.
Keywords: VINYL CARBAMATE; IMMUNOSUPPRESSION; ACTIVATION; RAT